Uncreative writing : managing language in the digital age - Goldsmith, Kenneth (Columbia University Press, 2011)
Can techniques traditionally thought to be outside the scope of literature, including word processing, databasing, identity ciphering, and intensive programming, inspire the reinvention of writing? The Internet and the digital environment present writers with new challenges and opportunities to reconceive creativity, authorship, and their relationship to language. Confronted with an unprecedented amount of texts and language, writers have the opportunity to move beyond the creation of new texts and manage, parse, appropriate, and reconstruct those that already exist. In addition to.